Analisis Keadilan Distributif dalam Alokasi Subsidi Pertanian: Tinjauan Ekonomi Islam - Septiana Ningrum; Subandi Subandi; Finny Ligery (KURAS Institute, 2024)
This study examines the distribution system of subsidized fertilizers in Kotagajah from the perspective of Islamic economic justice. Employing a qualitative field research design, data were collected through observation, in-depth interviews with distributors and farmer groups, and analysis of regulatory and academic sources, and were subsequently analyzed inductively using triangulation techniques. The findings indicate that procedurally the distribution mechanism adheres to the RDKK scheme and the “Six Right” principles; however, its implementation reveals three major pathologies: target displacement that marginalizes smallholder farmers, price distortions through sales above the government’s Highest Retail Price (HET), and excessive fertilizer consumption leading to artificial scarcity and ecological degradation. From the standpoint of Islamic economics, these practices represent deviations from the principles of justice (al-‘adl), trust (amanah), and the prohibitions of injustice (ẓulm) and excess (isrāf). The study concludes that the effectiveness of subsidized fertilizer distribution cannot be assessed solely through procedural compliance but must be grounded in moral integrity, institutional oversight, and a maṣlaḥah-oriented framework to ensure distributive justice and sustainable agricultural development. This study enhances the discourse on Islamic economics by highlighting public subsidy policies that incorporate fiscal instruments, distributive ethics, and ecological preservation. It also introduces a maslahah-based evaluation framework for policymakers to improve distribution monitoring, aiming to reduce information asymmetry and moral hazard at the grassroots level.